“Radical Empiricism” by W. James - Patkauskaitė, Jūratė (Problemos, 1983)
The classical genetic empiricism, as well as rationalism, was unable to ground the, nature of general concepts. W. James, having evaluated the shortcomings of the early empiricism, opposing rationalistic trend and ignoring the heritage of the classical German philosophy is striving to solve the traditional problems by a new version of “radical empiricism”. By introducing the concept of "pure experience" W. James aspires to avoid dualism of the subject and the object and to ground the nature of conceptual knowledge. This attempt, however, was unsuccessful and resulted in subjectivism.